Rapid Resolution of Megaesophagus by Low-dose Levothyroxine in a Hypothyroid dog with Mitral Valve Degeneration - Lee, Dohee; Yun, Taesik; Koo, Yoonhoi; Chae, Yeon; Kang, Byeong-Teck; Yang, Mhan-Pyo; Kim, Hakhyun (Journal of the Hellenic Veterinary Medical Society, 2022)
A 14-year-old intact female Maltese dog weighting 4.84kg was presented with acute regurgitation. At presentation, the dog was diagnosed with megaesophagus and primary hypothyroidism based on the radiography and thyroid-stimulating hormone stimulation test, respectively. Treatment was initiated with oral low-dose levothyroxine (0.0025 mg/kg b.w., orally, SID) considering underlying myxomatous mitral valve disease. Ten days after the management, the clinical and radiographic signs of megaesophagus were completely resolved. The dog was managed by levothyroxine administration with a gradual increase of the dose along with the monitoring of serum thyroxine concentrations since the dog was diagnosed with hypothyroidism. At 10 months after presentation, the dog continued to do well clinically. This is first case report describing rapid resolution of generalized megaesophagus after low-dose levothyroxine administration considering underlying cardiac disease in a hypothyroid dog.